Challenges with Conservation Genetics and Genomics in Neotropical Forest - Monteiro Siqueira, Marcos Vinicius Bohrer; Moraes Silvestre, Marcela Aparecida de [UNESP]; Tambarussi, Evandro Vagner [UNESP]; Francisconi, Ana Flávia; Zucchi, Maria Imaculada (Springer Nature, 2023)
Several accounts of the exceptional richness of neotropical forests were recognized by European peoples of the “New World”. For this reason, the colonization process in these regions were extractive. Unfortunately, we still have this cultural heritage, in which we exploit our biodiversity irrationally. In this context, we will discuss in this chapter the state of conservation of vegetation cover in neotropical regions, especially Brazil, due to the greater availability of information. Additionally, advances in recent years in this area of conservation genetics will be presented using genetic and molecular tools. We will also show the importance of studies related to population genetics to subsidize conservation programs. Furthermore, we will highlight the difficulties of public institutions of teaching and research to carry out this work, and how these are key pieces to propose strategies for the conservation, use and management of plant genetic resources.